Polymorphism of the cold receptor gene TRPM8 in native populations of Siberia: putative selective role of rs11563208 polymorphism in Northeast Asia - B. A. Malyarchuk; M. V. Derenko (Вавиловский журнал генетики и селекции)
The TRPM8 gene encodes the cold-activated receptor TRPM8, which has an important role in cold adaptation as well as in metabolic and immune responses. Previously, it has been found that polymorphic variants of the TRPM8 gene, which are present in human populations, are associated with different cold sensitivity. In the present study we have investigated variability of all exons and adjacent intronic sequences of this gene in samples of native populations of Siberia, including regional groups from Northeastern, Central, Southern and Western parts of Siberia. In 9 out of 21 variable loci revealed, the frequency of the derived alleles accounts for more than 10 % (loci rs28901637, rs11562975, rs10929319, rs28901644, rs7593557, rs12185590, rs10171428, rs11563208, and rs11563071). Different variants of these polymorphic loci, which are most frequent in native Siberians, generate 26 haplotypes. In addition to 7 haplotypes shared by all regional groups and present there at frequencies of 2–28 %, unique haplotypes were found in all regional samples. One of them characterized by derived allele T at rs11563208 locus is very interesting because it is spread at the frequency of 14 % only in Northeast Asia (in Koryaks and Chukchi). A synonymous substitution at rs11563208 locus may have a functional role because the amino acid residue (isoleucine at position 1016 of TRPM8 protein) corresponding to this locus is located in functionally important TRP-domain and, hence, it can influence thermoreception processes. It is assumed that the appearance of the haplotype carrying the rs11563208-T allele may be due to the necessity to counteract the inhibition of TRPM8 receptors by polyunsaturated fatty acids, which are typical of the traditional diet of native people of Northeast Asia (Siberian Eskimo, Chukchi and Koryaks).